The Role of Endoproteolytic Processing in Neurodegeneration - M. Wilson, Cornelia; Mushtaq, Gohar; A. Kamal, Mohammad; Terro, Faraj (CNS & Neurological Disorders - Drug Targets, 2016)
Endoproteolysis is a normal post-translational process in the eukaryotic cell that plays a role in protein evolution allowing protein catabolism and the generation of amino acids. Endoproteolytic cleavage regulates many crucial cellular processes including the activity of many proteins, their protein-protein interactions and the amplification of cell signals. Not surprisingly, disruption or alternation of endoproteolytic cleavage may be the root cause of many human diseases such as Alzheimer’s disease, Huntington’s disease and prion diseases. Most neurodegenerative diseases (ND) are caused by the build-up of misfolded proteins and the promotion of aggregation events. A common event that occurs in these ND is the alteration of endoproteolytic cleavage due to genetic mutations of the associated-proteases or target substrate. Endoproteolytic cleavage resulting in protein truncation has significant effects on the structure and function of a protein representing a common feature of ND. In this review, we will discuss the endoproteolytic cleavage events that lead to ND, namely Alzheimer’s disease, Huntington’s disease and prion diseases.
Keywords: prion disease